KLASIFIKASI IRIS SPECIES MENGGUNAKAN METODE K-NEAREST NEIGHBOR (KNN) - Sitorus, Zunaida; Nurliana, Nurliana; Selase, Septinur; Patmala, Desi; Nuraini, Sulhani; Aritia, Yusria; Margolang, Izwal Jamil (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract : Iris species classification is an important topic in the field of data mining and machine learning because it is commonly used as a benchmark dataset for classification methods. This study aims to design and implement an information system that can classify Iris flower species using the K-Nearest Neighbor (KNN) method. The dataset used in this research is the Iris dataset, which consists of 150 data records with four attributes: sepal length, sepal width, petal length, and petal width, and three classes, namely Iris Setosa, Iris Versicolor, and Iris Virginica. The KNN method works by calculating the distance between test data and training data using the Euclidean distance formula and determining the class based on the majority of the nearest neighbors. The results of the study show that the KNN method is able to classify Iris species accurately with a good level of performance. Based on the testing results, the developed system can assist users in identifying Iris species effectively and efficiently. In conclusion, the K-Nearest Neighbor method can be successfully applied in an information system for Iris species classification. Keywords: Classification, Iris Dataset, K-Nearest Neighbor, Data Mining, Machine Learning Abstrak : Klasifikasi spesies Iris merupakan topik penting dalam bidang data mining dan machine learning karena sering digunakan sebagai dataset standar dalam pengujian metode klasifikasi. Penelitian ini bertujuan untuk merancang dan mengimplementasikan sistem informasi yang dapat mengklasifikasikan spesies bunga Iris menggunakan metode K-Nearest Neighbor (KNN). Dataset yang digunakan adalah dataset Iris yang terdiri dari 150 data dengan empat atribut, yaitu panjang sepal, lebar sepal, panjang petal, dan lebar petal, serta tiga kelas yaitu Iris Setosa, Iris Versicolor, dan Iris Virginica. Metode KNN bekerja dengan menghitung jarak antara data uji dan data latih menggunakan rumus Euclidean Distance, kemudian menentukan kelas berdasarkan mayoritas tetangga terdekat. Hasil penelitian menunjukkan bahwa metode KNN mampu mengklasifikasikan spesies Iris dengan tingkat akurasi yang baik. Berdasarkan hasil pengujian, sistem yang dikembangkan dapat membantu pengguna dalam mengidentifikasi spesies Iris secara efektif dan efisien. Dengan demikian, metode K-Nearest Neighbor dapat diterapkan dengan baik dalam sistem informasi klasifikasi Iris Species. Kata Kunci : Klasifikasi, Dataset Iris, K-Nearest Neighbor, Data Mining, Machine Learning